Prevalence and factors associated with road traffic crash among bus drivers in Hanoi, Vietnam - La, Q.; Lee, Andy; Meuleners, Lynn; Duong, D. (Taylor and Francis, 2013)
Bus provides a main mode of public transport in Vietnam, but the risk of road traffic crash for bus drivers is unknown. This retrospective study estimated the crash prevalence among bus drivers in Hanoi, Vietnam, and identified driver characteristics affecting their crashes. Information on bus crashes for the period 2006–2009 was collected by interviewing drivers from five bus companies in Hanoi using a structured questionnaire. Logistic regression analysis was performed to determine pertinent risk factors affecting the crash prevalence for bus drivers. Of the total 365 participants recruited, 73 drivers reported 76 crashes, giving an overall crash prevalence of 20%. Among the crashed group, three drivers (4%) were involved in two crashes during the past 3 years. Crashes mainly occurred on streets or local roads (81%). Migrant worker (adjusted odds ratio (OR) 4.26, 95% confidence interval (CI) 2.20–8.25) and insufficient income perceived (OR 2.60, 95% CI 1.37–4.93) were identified to be significantly associated with the crash risk. Further prospective and qualitative studies are needed to provide detailed crash characteristics as well as behaviour and perception of bus drivers, so that an effective intervention can be developed to improve road safety and to prevent traffic injury of these drivers.